AN ANALYSIS OF GRAMMATICAL ERRORS IN SPEECH AT THE STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF MUHAMMADIYAH UNIVERSITY OF METRO ACADEMIC YEAR 2013/2014 - Septian Dwi Sondiana; Sudirman - - (Premise: Journal of English Education and Applied Linguistics, 2014)
The objectives of the research are to find out the types of grammatical errors in English students’ speech; to find out the percentage of grammatical errors in English students’ speech; to find out the factors influencing English students’ grammatical errors in their speech. Based on the data, the students have problem in producing verb group, errors in subject-verb agreement, errors in the use of articles, errors in the use of prepositions, errors in noun pluralization, errors in the use of pronouns, and errors in the use of conjunctions. It shows that Anisa made eleven sentences in 2 minutes 28 seconds. She made eight errors. Dewi made seven sentences in 1 minutes 57 seconds. She made five errors. Fatika made sixteen sentences in 4 minutes 14 seconds. She made eight errors. Fitri made sixteen sentences in 4 minutes 23 seconds. She made seven errors. Ibnu  made  ten sentences in 2 minutes 18 seconds. He made eight errors. Linda made fiveteen sentences in 3 minutes 7 seconds. She made eight errors. Musli made fourteen sentences in 2 minutes 39 seconds. She made six errors. Nyoman made twelve sentences in 3 minutes 43 seconds. He made nine errors. Pera made ten sentences in 2 minutes 23 seconds. She made seven errors. Sri made fourteen sentences in 6 minutes 34 seconds. She made eleven errors. And about the percentages of errors, here is the data; Anisa: 72,73% of errors; Dewi: 71,4% of errors; Fatika: 50% of errors; Fitri: 43,75% of errors; Ibnu: 80% of errors; Linda: 53,3% of errors; Musli: 42,8% of errors; Nyoman: 75% of errors; Pera: 70% of errors; Sri: 78,57% of errors. Based on interview, it shows it can be concluded the factors influence of English students’ grammatical errors in their speech when their speak using grammar rule. The internal factors are; The first, the students are still difficult to make feeling, for example; confident, feel scary, when they are speaking in public. The second, the students are not mastered in their skills. The third, the students are not have many vocabulay, so they can not express their idea to speak. The forth, the students are still think that grammar are not important to speak. For the external factors are; the first, the student  can not express their speaking because of their environment or comunity. The second, the teaching-learning process.